Community structure and exploitation pressure of giant clam in dedap island-abang waters batam - Meilanda, Yuria Liza; Efendi, Yarsi; Agustina, Fenny (STKIP Persada Khatulistiwa Sintang, 2025)
The community structure of Tridacnidae in the shallow coral waters of Dedap Island, Batam, has been analysed through a quantitative approach to reveal ecological dynamics and exploitation pressures from the surrounding communities. This study employed transect methods and ecological index analysis, including Shannon-Wiener diversity (H?), evenness (E), and Simpson's dominance (D) across five observation stations. The results indicate a high dominance of Tridacna crocea in locations with low exploitation pressure, whereas T. maxima and T. squamosa, which are still hunted by the local population, exhibit limited abundance. Pearson correlation revealed that dissolved oxygen (DO) has a strong positive relationship with H? and E, and a negative relationship with D, while temperature showed an inverse relationship. The integration of ecological analysis with socio-ecological factors revealed that anthropogenic exploitation pressures also shape community structure spatially. This study offers a holistic approach to the conservation management of Tridacnidae based on community participation and habitat zoning, while simultaneously addressing gaps in ecological and social research in the coral reef areas of western Indonesia.